Ilmu Pengetahuan Sebagai Pilar Peradaban - Kustiana Arisanti (Institut Ilmu Keislaman Zainul Hasan Genggong, 2018)
Islam is a rational religion and a scientific religion. As a rational and scientific religion the mark always lays the foundations that conform to scientific standards and can be proved by reason in various shari'ah and other rule provisions. Rasulullah Saw. as a carrier, spreader and proselytizer of Islamic Shari'a laid a solid foundation as a rational religion. This is seen in his words